Forebrain Organoids to Model the Cell Biology of Basal Radial Glia in Neurodevelopmental Disorders and Brain Evolution - Kaluthantrige Don, Flaminia; Kalebic, Nereo (Frontiers in Cell and Developmental Biology, 2022)
The acquisition of higher intellectual abilities that distinguish humans from their closest relatives correlates greatly with the expansion of the cerebral cortex. This expansion is a consequence of an increase in neuronal cell production driven by the higher proliferative capacity of neural progenitor cells, in particular basal radial glia (bRG). Furthermore, when the proliferation of neural progenitor cells is impaired and the final neuronal output is altered, severe neurodevelopmental disorders can arise. To effectively study the cell biology of human bRG, genetically accessible human experimental models are needed. With the pioneering success to isolate and culture pluripotent stem cells in vitro, we can now routinely investigate the developing human cerebral cortex in a dish using three-dimensional multicellular structures called organoids. Here, we will review the molecular and cell biological features of bRG that have recently been elucidated using brain organoids. We will further focus on the application of this simple model system to study in a mechanistically actionable way the molecular and cellular events in bRG that can lead to the onset of various neurodevelopmental diseases.